REGRESI PANEL TINGKAT PENGANGGURAN TERBUKA KABUPATEN/KOTA PROVINSI NUSA TENGGARA BARAT - Safaat Yulianto; Dinar Ade Kurniawan (VARIANCE: Journal of Statistics and Its Applications, 2021)
The main problems that developing countries facing especially Indonesia is the problem of job-field limitations. Increasing the number of people followed by increasing labor force will increase unemployment if it does not balance with increasing in job opportunities. Some research has been conducted to examine factors that affect the unemployment rate, especially open unemployment. The open unemployment may differ from one area to another, as well as changes from time to time, so open unemployment level problems are more accurately analysed using the panel data regression. A significant factor affecting the open unemployment rate in the Southeast Nusa Province is the percentage of the poor and the percentage of the working people 15 years old above high school.